Teaching, Technology, Textuality - Hanrahan, Michael. author. aut Link
XVI, 193 p. 7 illus.
Keywords: This collection of original essays discusses the implications of the new media for the creation, delivery and assessment of English studies. Strategies by which digital technologies can serve professional, scholarly and pedagogical needs in a completely new way are explored in the context of the role and mission of humanities in the electronic age.